2014
DOI: 10.1002/kin.20844
|View full text |Cite
|
Sign up to set email alerts
|

Master Equation Modeling of the Unimolecular Decompositions of α‐Hydroxyethyl (CH3CHOH) and Ethoxy (CH3CH2O) Radicals

Abstract: The unimolecular decomposition of two radical isomers of C2H5O (CH3CH2O/ethoxy, CH3CHOH/α‐hydroxyethyl) are investigated by means of Rice–Ramsperger–Kassel–Marcus/master equation simulations in helium and nitrogen bath gases on an accurate one‐dimensional potential energy surface. For ethoxy, simulations are carried out between temperatures of 406 and 1200 K and pressures of 0.001 and 100 atm. For CH3CHOH, simulations are carried out between temperatures of 800 and 1500 K and pressures of 0.001 and 100 atm. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 54 publications
0
11
0
Order By: Relevance
“…Calculations from Dames 34 predict that about 92% of CH 3 C(H)OH will decompose to either acetaldehyde or vinyl alcohol, while 8% will form formaldehyde. Since vinyl alcohol will tautomerize to acetaldehyde, R1499 will overwhelmingly lead to acetaldehyde as the closed shell product.…”
Section: Isopropanol Decompositionmentioning
confidence: 99%
See 1 more Smart Citation
“…Calculations from Dames 34 predict that about 92% of CH 3 C(H)OH will decompose to either acetaldehyde or vinyl alcohol, while 8% will form formaldehyde. Since vinyl alcohol will tautomerize to acetaldehyde, R1499 will overwhelmingly lead to acetaldehyde as the closed shell product.…”
Section: Isopropanol Decompositionmentioning
confidence: 99%
“…6,[30][31][32][33] Fission of the C−O bond has too large a barrier to play a significant role. 30 Scheme 1 shows the main unimolecular reactions of isopropanol: dehydration (R1498) produces propene (C 3 H 6 ) and water; C−C bond fission (R1499) produces a methyl radical (CH 3 ) and a CH 3 CHOH radical, whichaccording to calculations by Dames 34 -will decompose to either acetaldehyde (CH 3 CHO) or formaldehyde (CH 2 O).…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that the further oxidation of CH 3 O and CH 2 OH radicals by HO 2 produces more stable species like formaldehyde, formic acid, or hydrogen peroxide Equations to . Thus, the reactions of CH 3 CH 2 O and CH 3 CHOH with HO 2 are one of the most important degradation processes in the atmosphere CH3CH2OHCH3CH2normalO+normalH CH3CH2OHCH3CHOH+normalH CH2OH+HO2CH2normalO+H2O2 CH2OH+HO2HCOOH+H2normalO CH3normalO+HO2CH2normalO+H2O2 …”
Section: Introductionmentioning
confidence: 99%
“…[26] Thus, the reactions of CH 3 CH 2 O and CH 3 CHOH with HO 2 are one of the most important degradation processes in the atmosphere. [27][28][29][30][31][32][33][34][35][36][37] CH 3 (5) There is no any experimental and theoretical report in the literature about the reactions of CH 3 CH 2 O + HO 2 and CH 3 CHOH + HO 2 . By contrast, a theoretical study on the singlet and triplet reaction mechanisms of CH 3 O + HO 2 and CH 2 OH + HO 2 has been reported at CCSD (T)/aug-cc-pVTZ//MPWB1K/6-31 + G (d,p) level of theory by Mousavipour and co-workers, [38] which provides the meaningful information to the reaction mechanism that involved HO 2 radical.…”
Section: Introductionmentioning
confidence: 99%
“…The α-hydroxyethyl radical (CH 3 CHOH) is presumably the major product of Habstraction from ethanol. For the decomposition of CH 3 CHOH (R6), the rate constants are taken from an RRKM study by Dames [41] who predicted the major branch, CH 3 CHOH(+M) = CH 3 CHO+H(+M) (R6a) to be faster by up to one order of magnitude compared to an earlier calculation by Xu et al [46].…”
mentioning
confidence: 99%